Ideological Foundations in the Development of the Arabic Language Curriculum - Isop Syafei; Ade Arip Ardiansyah; Dadan Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the ideological foundations in the development of the Arabic language curriculum as part of a strategic effort to shape national identity, Islamic values, and cultural integrity within the educational system. The Arabic language curriculum functions not only as a medium for language learning but also as a means of internalizing educational ideologies that reflect Islamic, national, and humanistic visions. The study aims to identify and analyze the ideological dimensions that influence the direction and content of the Arabic language curriculum, particularly in Islamic educational institutions. A qualitative approach is employed using a literature review method, analyzing various sources related to educational ideology, curriculum, and language policy. Data were collected through documentation of primary and secondary sources and analyzed using descriptive-analytical methods. The findings reveal three main ideological foundations in the development of the Arabic language curriculum: religious ideology (Islam as a core value), national ideology (Arabic as part of the heritage of Indonesian Muslims), and humanistic ideology (character development and global ethics). These findings affirm that the Arabic language curriculum must be developed with consideration of ideological contexts that strengthen students’ identity as faithful, knowledgeable, and morally upright individuals.